Minimal Levelized Cost Cooling-Based Atmospheric Water Generator Using a Hybrid Solar-Wind Off-Grid Power Source - Chavez-Orostica, H; Riquelme-Vera, E (Institute of Electrical and Electronics Engineers Inc., 2023)
In response to the water scarcity in rural and isolated areas with difficult access to water resources, this study presents a mathematical model for a water production system that utilizes a solar-wind hybrid generation source. The system is based on Cooling-based AtmosphericWater Generator, capable of producing up to 5,000 liters of water daily from the air, with its own purification and storage system. The main objective is to develop an optimization model that minimizes the levelized cost of water and obtains the optimal sizing of the hybrid generation plant and the storage system. This model is implemented in the software AIMMS to determine the optimal condition and analyze the behavior of the variables. The results of the optimization model simulation are compared with a previously proposed power supply design, validating the utility of the model. © 2023 IEEE.